The Construction of Sports Health Management Model Based on Deep Learning - Junniao Meng; Song Wang (Applied Bionics and Biomechanics)
Deep learning is a new direction in the field of machine learning. It learns the inherent laws and representation levels of sample data. The information obtained in the learning process plays a great role in interpreting data such as text, images, and speech. Health management refers to the process of identifying, evaluating, and effectively intervening the health of individuals or groups of people. The purpose of this article is to build a sports health management model based on deep learning, to train students to actively take physical exercises, thereby promoting their physical fitness. This article first introduces related concepts such as deep learning and convolutional neural networks and then conducts an experimental exploration on the combination of convolutional neural networks and multilayer perceptrons. Secondly, this article designs a plan for sports health management of sports interventions and compares and analyzes the data before and after health management. The experimental results show that the average value of the overall health dimension after the experiment has reached 85.28, and the average value has reached a very high score, indicating that exercise intervention can effectively improve the physical fitness of students. At the same time, it improves the physical condition of students.